Rancang bangun sistem manajemen energi baterai otomatis untuk cadangan listrik rumah dengan kapasitas 300 watt - Muki Satya Permana; Toto Supriyono; Hery Sonawan (BKS-TM Indonesia, 2025)
Unstable electricity supply in rural areas is a significant challenge that disrupts community activities. The inadequate quality of the electricity grid and supply fluctuations demand a reliable and independent energy backup solution. This study proposes the design of a Battery Energy Storage System (SMEB) that integrates an inverter, a flexible battery charging system, and an automatic power source switching mechanism. A literature review indicates a research gap regarding the use of alternators in vehicles as a battery charging source, which offers a practical solution, especially in remote locations. This study aims to design and build a prototype SMEB equipped with an integrated inverter, develop an efficient automatic battery charging system from various sources (the PLN electricity grid, PV, and alternator), and implement a reliable Automatic Transfer Switch (ATS) to ensure continuous electricity supply. The main contribution of this study is the creation of a portable, efficient SMEB prototype with plug-and-play capabilities for charging from various sources, including alternators. This system is designed to operate independently (stand-alone) and provides a practical solution to electricity supply problems.